Odpowiedź :
Odpowiedź:
a)
5x + 2 = 3x + 16
5x - 3x = 16 - 2
2x = 14 /:2
x = 7
b)
- 3x + 4 = - 5x + 6
- 3x + 5x = 6 - 4
2x = 2 / : 2
x = 1
c)
- 5 (x - 3) + 2 = - 9x + 1
- 5x + 15 + 2 = - 9x + 1
- 5x + 9x = 1 - 15 - 2
4x = - 16 /: 4
x = - 4
d)
8 = 6 (x - 1) - 4x
8 = 6x - 6 - 4x
- 6x + 4x = - 6 - 8
- 2x = - 14 / : (- 2)
x = 7
e)
(x + 1) / 3 + (2x - 2) / 2 = (2x - 1) / 6 / * 6
2x + 2 + 6x - 6 = 2x - 1
2x + 6x - 2x = - 1 - 2 + 6
6x = 3 / : 6
x = 1/2
Szczegółowe wyjaśnienie:
A. 5x-3x=16-2;
2x=14|2;
x=7
B. -3x+5x=6-4
2x=2|2
x=1
C. -5x+15+2=-9x+1
-5x+9x=1-15-2
4x=-16|4
x=-4
D. 8=6x-6-4x
-6x+4x=-6-8
-2x=-14|-2
x=7
E. (x+1)/3+(2x-2)/2=(2x-1)/6 |*6
2(x+1)+3(2x-2)=2x-1
2x+2+6x-6=2x-1
2x+6x-2x=-1-2+6
6x=3|6
x=0,5
2x=14|2;
x=7
B. -3x+5x=6-4
2x=2|2
x=1
C. -5x+15+2=-9x+1
-5x+9x=1-15-2
4x=-16|4
x=-4
D. 8=6x-6-4x
-6x+4x=-6-8
-2x=-14|-2
x=7
E. (x+1)/3+(2x-2)/2=(2x-1)/6 |*6
2(x+1)+3(2x-2)=2x-1
2x+2+6x-6=2x-1
2x+6x-2x=-1-2+6
6x=3|6
x=0,5